2016
DOI: 10.1016/j.bjhh.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous universal donors: the reality of the Hemocentro in Belo Horizonte, Minas Gerais

Abstract: BackgroundThe term dangerous universal blood donor refers to potential agglutination of the erythrocytes of non-O recipients due to plasma of an O blood group donor, which contains high titers of anti-A and/or anti-B hemagglutinins. Thus, prior titration of anti-A and anti-B hemagglutinins is recommended to prevent transfusion reactions.ObjectiveThe aim of this study was to estimate the frequency of dangerous universal donors in the blood bank of Belo Horizonte (Fundação Central de Imuno-Hematologia – Fundação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the present study significant association between high titer and age was observed. There are few publications that have described a relationship between titer and age 10,11 mostly pointing out higher prevalence among young age group. Study by Rachel beddard at al showed a positive correlation between donor age and high titre of antibody.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study significant association between high titer and age was observed. There are few publications that have described a relationship between titer and age 10,11 mostly pointing out higher prevalence among young age group. Study by Rachel beddard at al showed a positive correlation between donor age and high titre of antibody.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there were more females than males with higher antibody titer levels, with significantly more females than males with anti-A, which may be caused by sensitization during pregnancies. 13,16,22 . High titers of anti-A haemolysins were reported to be associated with females 16 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable with high-titer cases in Brazilian (30%) and Italian (27%) studies. 37,38 Our study was an in vitro investigation that, for the first time, showed the most frequently encountered titers of ABO antibodies in Iranian donors and compared titer values in male and female donors as well as within age ranges of these donors. We note that a clinical study is also required to determine potentially clinically critical titers in practice.…”
Section: Number Of Casesmentioning
confidence: 99%